(untitled) (Mustansiria Dental Journal, 2019)
Aim: The point of the study was to assess the prevalence of apical periodontitis and frequency of endodontic treatment in an Iraqi population. Materials and methods: Panoramic radiographs of 300 Iraqi subjects 18-60 years old. The periapical status of all teeth (with the exception of third molars) was examined using periapical index scoring system (PAI). Information were investigated statistically using the Chi-squared test at the significance level of p<0.05. Results: Out of 5822 examined teeth belonging to 300 patients 156 had one or more teeth with apical periodontitis (PAI 3-5) and 253 individuals had one or more endodontically treated teeth. Conclusions: The discoveries of the exhibit examination come into concurred upon with different investigations which accentuate that a worldwide improvement in the quality of root canal treatment in general dental practice is required to promote periradicular health.